2001
DOI: 10.1146/annurev.ento.46.1.667
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL CONTROL OF LOCUSTS AND GRASSHOPPERS

Abstract: Control of grasshoppers and locusts has traditionally relied on synthetic insecticides, and for emergency situations this is unlikely to change. However, a growing awareness of the environmental issues associated with acridid control as well as the high costs of emergency control are expanding the demand for biological control. In particular, preventive, integrated control strategies with early interventions will reduce the financial and environmental costs associated with large-scale plague treatments. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
257
0
12

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(272 citation statements)
references
References 139 publications
3
257
0
12
Order By: Relevance
“…Preliminary simulated field tests with a B. bassiana isolate in Brazil indicated that activity against T. infestans may be reduced compared to laboratory conditions . The recent development of effective oil-formulations of entomopathogenic fungi is opening new possibilities for environmentally safe control strategies (Lomer et al 2001). We report here on field and semi-field tests with oil-formulated B. bassiana in Central Brazil to control peridomestic T. sordida.…”
mentioning
confidence: 99%
“…Preliminary simulated field tests with a B. bassiana isolate in Brazil indicated that activity against T. infestans may be reduced compared to laboratory conditions . The recent development of effective oil-formulations of entomopathogenic fungi is opening new possibilities for environmentally safe control strategies (Lomer et al 2001). We report here on field and semi-field tests with oil-formulated B. bassiana in Central Brazil to control peridomestic T. sordida.…”
mentioning
confidence: 99%
“…There have been many attempts to use this fungus as a practical biocontrol agent against many insect pests, from termites in USA (Copping, 2001) to grasshoppers and locusts in Africa (Lomer et al, 2001). M. anisopliae isolates used in this study, especially KTU-2, KTU-27 and KTU-40, also showed good activity against larvae of the willow leaf beetle.…”
Section: Disscussionmentioning
confidence: 80%
“…outbreak in forestry in Poland and North America with the products of B. thuringiensis subspecies kurstaki (Btk) [6], Pine caterpillar management with B. bassiana in China [7], locust control with Metarhizium anisopliae var. acridium in Africa, Australia and China [8], sugarcane spittle bug management by Metarhizium anisopliae in Brazil, rubber lace bug control with Sporothrix insectorum, corn borer management with B. bassiana in Europe and USA [3], and European pine sawfly management with NPV in Europe and North America [9]. The main advantages of these biocontrol agents are their specificity to target pests, safety to the non-target organism, they do not cause ill effects on environment and human health and can be used against pests which develop resistance to the conventional insecticides, they fit as ideal components in integrated pest management (IPM) and also in organic farming systems.…”
Section: B Ramanujam Et Almentioning
confidence: 99%